Preventive Effects of Low-dose Dexamethasone for Delayed Adverse Events Induced by Carboplatin-based Combination Chemotherapy - TAKIGUCHI, Yoshiharu; TANAKA, Hiroaki; DOI, Chiaki; KANAJI, Nobuhiro; ISHIDA, Toshihiko; KAWAZOE, Hitoshi; FUKUOKA, Noriyasu; HOUCHI, Hitoshi; BANDOH, Shuji (YAKUGAKU ZASSHI, 2007)
We performed a retrospective study to examine the protective effect of low-dose dexamethasone (DEX) on delayed adverse events induced by carboplatin (CBDCA)-based combination chemotherapy in patients with thoracic tumors. Low-dose DEX (4-8 mg/day) was administered on day 1 and after, in addition to a serotonin 5-HT3 receptor antagonist. The acute adverse events (day 1) were well controlled in the patients with or without co-treatment of DEX. On the other hand, the delayed nausea, emesis, anorexia, and fatigue after day 2 failed to be controlled by 5-HT3 antagonist alone. Co-treatment with DEX significantly suppressed the grade of the delayed adverse events during days 2-10. The mean ratio of complete protection during days 2-10 were significantly higher in the DEX-treated group compared with the non-DEX-treated group. These results reveal that low-dose DEX is a clinically effective treatment for the prevention of delayed adverse events induced by CBDCA-based combination chemotherapy.